Correlation of Gleason Grading and Prognostic Immunohistochemistry Markers (Human Epidermal Growth Factor Receptor 2/neu and Androgen Receptor) in Prostatic Core Needle Biopsy: A Study in a Tertiary Care Center - Senapati, Utsha; Sengupta, Moumita; Datta, Chhanda; Chatterjee, Uttara; Pal, Dilip Kumar; Das, Diya; Poddar, Piyali (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Worldwide prostate cancer is the most common cause of cancer and the second leading cause of cancer death among men. Transrectal ultrasound-guided core needle biopsies are the diagnostic modalities which help in proper categorization and grading of prostatic carcinoma, thus facilitating individualized treatment. These biopsies are the primary source for performance of additional diagnostic immunohistochemical testing for basal cell-associated markers to rule out the morphological mimicker and prognostic markers such as androgen receptor (AR) and human epidermal growth factor receptor 2 (HER2)/neu. Materials and Methods: A prospective, observational study was conducted in the department of pathology in collaboration with department of urosurgery of a tertiary care hospital. One hundred and nineteen patients diagnosed with prostatic nodules were included in this study. Values of serum prostate-specific antigen were recorded. Tissue for histopathological study was obtained in the form of core needle biopsy, and Gleason grade was calculated in all malignant cases. Immunohistochemistry for p63 and alpha-methylacyl-CoA racemase was performed as an additional test in premalignant cases. Prognostication of the prostate cancer cases was done using AR and HER2/neu. Results: A total of 119 cases aged between 20 and 90 years were included in this study. Malignant lesions reveal an increase in the percentage of AR staining in comparison to the benign glandular structure. The Gleason score with higher value (8–9) showed increased expression of HER2/neu receptor. Conclusion: Critical histopathological analysis of core needle biopsy along with immunohistochemical evaluation maximizes the diagnostic accuracy in prostate cancer cases and also helps in prognosis assessment.
Keywords: Androgen receptor; human epidermal growth factor receptor 2/neu; prostatic cancer; serum prostatic-specific antigen; transrectal ultrasound-guided core needle biopsies